Jointness in Bayesian Variable Selection with Applications to Growth Regression - Ley, Eduardo; Steel, Mark F. J. (2012)
The authors present a measure of jointness to explore dependence among regressors in the context of Bayesian model selection. The jointness measure they propose equals the posterior odds ratio between those models that include a set of variables and the models that only include proper subsets. They show its application in cross-country growth regressions using two data-sets from the model-averaging growth literature.